Effect of Joule heating on steady MHD convective micropolar fluid over a stretching/shrinking sheet with slip flow model (Journal of Naval Architecture and Marine Engineering, 2021)
The effect of joule heating on steady two dimensional flow of an incompressible micropolar fluid over a flat deformable sheet is analyzed when the sheet is stretched with a slip in its own plane. The effects of first and second order slips with dissipative heat energy are considered in the present study. The numerical solution to coupled non-linear differential equations is obtained using the Runge-Kutta method of fourth order with shooting technique. The important findings of the present study are: Due to shrinking effect, temperature increases more than that of stretching which is analogous to contraction and expansion forming the basis of heat engine, transporting thermal energy to mechanical energy. The thermal buoyancy overpowers the inertia force. The second order slip is favorable for flow stability in both stretching and shrinking of the deformable surface.